Analisis Tindak Tutur Menyatakan Pendapat dalam Drama Seri “1 Rittoru No Namida” - Asteria Permata Martawijaya (Journal of Japanese Language Education and Linguistics, 2019)
Expressing opinion is a speech act that can be considered unpolite if delivered in a direct speech. Therefore, when expressing their opinions Japanese people often use various speech act constructions so that their opinions are not too straight to the point. This is done in order to respect and maintain the interlocutor’s feeling. In this study, the author examines speech acts expressing opinions in everyday conversation by looking at the construction used and its meaning. This research is limited to speech acts expressing opinions or facts in conversations on 1 Rittoru no Namida drama series. The method that used in this reseach is descriptive method. From the results of the study it was found that when expressing opinions or facts, speakers in the drama series 1 Rittoru no Namida used various constructions. The most widely used construction is guess construction. In addition, the construction of approval requests construction, avoidance construction, considerations construction, and elliptical construction are also used on the conversations.